Studies on Quasi-Static and Fatigue Crack Propagation Behaviours in Friction Stir Welded Joints Using Peridynamic Theory - Fei Wang; Yu’e Ma; Yanning Guo; Wei Huang (Advances in Materials Science and Engineering)
The friction stir welding (FSW) technology has been widely applied in aircraft structures. The heterogeneity of mechanical properties in weld and the hole in structure will lead the crack to turn. Peridynamics (PD) has inherent advantages in calculating crack turning. The peridynamic theory is applied to study the crack turning behaviour of FSW joints in this work. The compact tension (CT) samples with and without a hole are designed. The crack propagation testing under quasistatic and fatigue loads are performed. The peridynamic microplastic model is used and a three-stage fatigue calculation model is developed to simulate the quasistatic fracture and the fatigue crack growth. The results predicted by the peridynamic models are compared with the experimental ones. The effects of welding direction on quasistatic and fatigue crack propagation behaviours are investigated and the effect of hole position on crack path geometry is also studied. It is shown that the crack turning in FSWed CT samples can be captured by the peridynamic microplastic and the three-stage fatigue calculation models. The peridynamic crack growth rates agree with the experimental results. For CT specimen without a hole, the crack turns into the weld zone where the material is softer. The effect of welding direction on crack growth rates is not obvious. For CT sample with a hole, the crack propagation direction has been mainly controlled by the hole location and the welding direction has a slight effect on crack path.